Maritime Piracy as a Challenge to Maritime Governance: A Critical Analysis of Counter Piracy in the Gulf of Guinea - Fuller, Emma-Jane (Department of Political Studies, 2023)
The Gulf of Guinea, endowed with vital and strategic resources, has for centuries served as an important region economically, socially, and politically. Since 2011, a substantial amount of time, research, human and financial resources have been dedicated towards this region, specifically, towards eradicating the threat of maritime piracy. Incidences of maritime piracy in the Gulf of Guinea is not a recent phenomenon. While not new, the political interest in piracy has grown. Today, maritime piracy in the Gulf of Guinea has become a significant element in the security make up of Africa, involving a myriad of actors through various forms and forums to counter the perceived threat it poses to international peace and security. A common question that informs the study of maritime piracy is ‘What threat does piracy pose to international security?'. This dissertation instead seeks to understand why piracy in the Gulf of Guinea is conceptualised as a major threat to maritime security, and how the phenomenon of maritime piracy is governed. Through this, it strives to understand what interests are protected through counter-piracy governance. The escalation of piracy is argued to be part and parcel of the growing global interest in the opportunities the Gulf bestows. The rush to address it is therefore motivated by the threat piracy poses to international interests, including energy, trade and commerce security. Given the growing international, regional, and national fixation on developing the ‘blue economy', and in the context of climate change and the history of inequitable resource governance, it is ever more critical to interrogate the ways in which the maritime space is governed and the types of behaviours this space accepts and rejects.